PARTISIPASI MASYARAKAT DALAM MENGGERAKKAN KEBERLANJUTAN PARIWISATA BERBASIS LINGKUNGAN DI DESA CARANGSARI KABUPATEN BADUNG - Lia Yasmita (Media Bina Ilmiah, 2023)
Tourism plays a very important role in increasing people's income in an area, in the province of Bali the tourism sector is one of the important sectors in increasing regional own-source income, it is very unfortunate if current tourism management does not involve the community in efforts to maintain natural ecosystems and the environment and maintain local wisdom that aims to sustain tourism and the environment. This research was conducted with the aim of analyzing the participation of local communities in the development of the Carangsaru Tourism Village in Petang District, Badung Regency. Data collection was carried out using a qualitative approach. The results of the study show that community participation in the management of tourist villages is still quite low, due to the low understanding of the community in managing tourism so that it is necessary to manage institutions from the community, Bumdesa, government that work together to be able to highlight creative ideas that can later give uniqueness to the village Carangsari Tourism, with the hope of benefiting the welfare of the community, revitalizing local culture and environmental conservation with the aim of tourism sustainability.